THE EFFECTIVENESS OF THE COLLECTION OF PROFESSION ZAKAT AND ITS ACCOUNTABILITY ON BAZNAS (CASE STUDY IN LOCAL GOVERNMENT IN TASIKMALAYA REGENCY) - Garini, Filia (Indonesian Journal of Islamic Business and Economics (IJIBE), 2019)
Profession Zakat through the payroll system is one of the collection procedures that are expected to help increase zakat acceptance in general. Badan Amil Zakat Nasional (BAZNAS) Tasikmalaya Regency is an official government institution that is trusted to manage and distribute zakat and it is expected to be an accountable institution. Using qualitative descriptive method to illustrate the true depiction and case study approach to explain specifically about the phenomena of the effectiveness of the collection of profession zakat and accountability of BAZNAS Tasikmalaya Regency. The results of this study indicate that the procedure of collecting zakat through the payroll system has been effective, seen from the achievement of profession zakat funds per year and also the calculation of Collection Ratio based on Zakat Core Principles. The financial statements made by BAZNAS Tasikmalaya Regency still not perfect, there are several components that have not been prepared so that the financial statement of BAZNAS Tasikmalaya Regency has not yet in accordance to Shari’a Financial Accounting Standard (SAK Syari’ah) No. 109 "Accounting for Zakat and Infaq/Sadaqah".